GE_GERICHTE PS/34/2013 vom 2. April 2014 - GE Cour de justice (2014)
CONDITION DE RECEVABILITÉ; PROCÉDURE ADMINISTRATIVE; COMPÉTENCE RATIONE MATERIAE; DÉLAI; CONNAISSANCE; RETARD | LOJ.128; CPP.439; LACP.5; LACP.40; CPP.396